1983
DOI: 10.1210/jcem-56-6-1294
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Removal of Insulin in Normal Man: Dose Response to Endogenous Insulin Secretion*

Abstract: The hepatic extraction of insulin in normal man was evaluated by kinetic analysis of peripheral insulin behavior in the plasma following stimulation of endogenous insulin secretion. Prehepatic insulin production was determined by deconvolution of plasma connecting peptide behavior (C-peptide) and hepatic extraction of the secreted insulin determined with a three-compartment model for hepatic, vascular, and extravascular plasma spaces. Three dosages of oral glucose (10, 25, and 100 g) administered to normal vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
87
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 30 publications
10
87
0
1
Order By: Relevance
“…The minute-to-minute adaptive changes in insulin clearance by the liver reported here in vivo reflect greater extraction of the insulin within than between insulin secretory bursts. The fact that absolute insulin clearance increases with insulin concentration (6,31) agrees with the present observations that the liver clears larger insulin secretory bursts to a greater extent than smaller insulin pulses, given that at least 70% of insulin secretion is pulsatile. In addition, analyses based on direct portal-vein catheterization established an ϳ100-fold higher amplitude of insulin concentration oscillations in the portal vein than in the peripheral circulation in humans (18).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The minute-to-minute adaptive changes in insulin clearance by the liver reported here in vivo reflect greater extraction of the insulin within than between insulin secretory bursts. The fact that absolute insulin clearance increases with insulin concentration (6,31) agrees with the present observations that the liver clears larger insulin secretory bursts to a greater extent than smaller insulin pulses, given that at least 70% of insulin secretion is pulsatile. In addition, analyses based on direct portal-vein catheterization established an ϳ100-fold higher amplitude of insulin concentration oscillations in the portal vein than in the peripheral circulation in humans (18).…”
Section: Discussionsupporting
confidence: 90%
“…The calculated fractional hepatic insulin extraction reported in the present study is higher than the estimated ϳ50% in the dog (2,4) but consistent with values reported in most human studies (5)(6)(7)44). In particular, based on a similar hepatic-vein sampling technique, hepatic first-pass extraction of insulin has been estimated as 70 -85% by different groups (7,45,46).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Normal glucose metabolism is achieved at the expense of basal and stimulated hyperinsulinaemia. The higher insulin levels are mainly due to the systemic rather than the physiological portal venous drainage of islet cell secretory products (Diem et al 1990a) with reduced first pass hepatic extraction of insulin (Eaton et al 1983). However, as discussed by Diem et al (1990a), basal elevated insulin and C-peptide levels in pancreas recipients may be a physiological response by the graft to increased glucose output from the liver.…”
Section: Discussionmentioning
confidence: 99%